Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Re visions, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

The lesbian postmodern - Doan, Laura L. (Between men--between women, 1994)
Tous originaux de ce volume, ces essais évocateurs rédigés par des chercheureuses tels que Robyn Wiegman, Elizabeth Grosz et Judith Roof examinent un domaine encore intact de la critique littéraire et culturelle et de la théorie du genre, une postmodernité spécifiquement lesbienne. Les essais retracent, d’une part, comment certaines théories et productions culturelles lesbiennes mettent en avant une politique de différence et de marginalité et critiquent ainsi l’hégémonie patriarcale et hétérosexuelle. D’un autre côté, certains essais soulignent comment une esthétique postmoderne, avec sa valorisation de la différence, de la pluralité sexuelle et du flou des genres, contribue à la production culturelle lesbienne. Parmi les sujets abordés figurent les définitions changeantes des termes lesbien et postmoderne ; le potentiel et danger de ce nouveau territoire conceptuel dans la théorie, la représentation littéraire et visuelle et la culture populaire ; la lesbienne dans le cinéma hollywoodien ; les actrices Jodie Foster et Sandra Bernhard ; et des œuvres de Jeanette Winterson, Michelle Cliff et Gloria Anzaldua. Tout au long, les contributeurices abordent les questions et enjeux interdépendants de classe, de race, d’ethnicité, de postcolonialisme et de marchandisation.
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; patriarcat; personnes lesbiennes; postmodernisme; sexisme; système colonial; systèmes d'oppressions; études littéraires

L'écrivain - Brossard, Nicole (La nef des sorcières, 1992)
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*; études littéraires

La nef des sorcières - Guilbeault, Luce; Blackburn, Marthe; Théoret, France; Gagnon, Odette; Blais, Marie-Claire; Pelletier, Pol; Brossard, Nicole; Guilbeault, Luce (L'Hexagone, 1992)
La création au Théâtre du Nouveau Monde de La nef des sorcières, pièce composée de sept textes d’auteures différentes, est reconnue comme un moment capital dans l’émergence du théâtre féministe militant au cours des années 1970 et 1980. En ce qui concerne la réception de ce spectacle et du texte publié, l’attention du public et de la critique se dirigeait surtout vers la thématique féministe véhiculée par la pièce et le commentaire qui s’y faisait sur le fonctionnement du patriarcat dans la vie privée des femmes. Cependant, l’objectif des auteures et des comédiennes dépassait largement le simple commentaire social. Ce n’était pas leur intention de réduire la scène théâtrale à une simple tribune politique. Luce Guilbeault, qui initia le projet et s’y engagea comme metteure en scène, auteure et comédienne, voulait avec les autres, en plus de susciter des discussions, ébranler les fondements sexistes du théâtre, élargir l’espace de l’imaginaire collectif, transformer la symbolique masculiniste de la culture québécoise, et élargir l’horizon d’attente de l’auditoire. Quand son Actrice en folie subit un trou de mémoire et enlève son costume dès son entrée en scène, c’est une ouverture remarquable au spectacle expérimental et à l’invention d’une nouvelle théâtralité au féminin qui se fait jour. C’est alors que commence la remise en cause radicale des pratiques, des codes, des règles et des conventions du jeu, des langages et de la forme canoniques du théâtre qui permettent depuis des millénaires l’esthétisation par le théâtre des idéologies et des fantasmes dominants sexistes.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

L'interloquée ; Les oubliées de l'oubli ; [et] Dé/générée - Causse, Michèle (Trois, 1991)
« L’androlecte est en effet un soliloque. C’est la production mentale, disons la pathologie langagière, de l’Andros qui, victime d’une faille principielle, n’a pas su, pas pu, pas voulu accéder au chiffre deux et qui, s’étant érigé en seul locuteur, n’a pas eu d’autre interlocuteur que lui-même. Avant même de parler, une femme en "Androlecte est inter-loquée". Soit au sens propre "interdite-interrompue". Le dictionnaire – depôt sacré des mots de l’androlecte – ne donne-t-il pas comme exemple cette phrase, ô combien illuminante: "Faute d’interlocuteur, elle se parlait à elle-même". (Petit Robert, Léon Bloy). Bécassine ayant cru sans doute dans le langage comme communication. » p.15 éditions Trois, 1990
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; sexisme; systèmes d'oppressions; études littéraires

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

C'est le soleil qui m'a brûlée - Beyala, Calixthe (J'ai lu. Roman, 1988)
"La tête dans les odeurs de l'homme, la bouche contre son sexe, elle se dit qu'il est devenu complètement fou, qu'elle est devenue complètement folle (...). Dans l'état actuel de l'histoire, quoi qu'elle fasse, quoi qu'elle dise, elle aura toujours tort. L'homme c'est lui." Cameroun. Chaleur humide, ciel hypnotique. Dans le bidonville où elle a grandi, abandonnée par sa mère, Ateba cherche avec désespoir sa place dans une société où la femme n'a qu'un droit : se taire. Ecartelée entre plusieurs sentiments contraires, la jeune fille, le ventre en feu, la haine au coeur, est certaine qu'elle peut devenir un jour la plus forte. Incapable de se résoudre à concilier sexe et asservissement, elle refuse de passer sa vie à genoux.--Quatrième de couverture.
Keywords: afrique; afro-féminisme; approches et analyses; arts; cameroun; cours; discipline; féminisme africain; lit2815; premier cycle; roman; régions géographiques; sexisme; systèmes d'oppressions; études littéraires

The Feminist Critique of Art History - Gouma-Peterson, Thalia; Mathews, Patricia (The Art Bulletin, 1987)
Art criticism and art history from a feminist perspective are recent phenomena, emerging only during the last fifteen years. They have, in their short history, moved from a first generation in which "the condition and experience of being female" was emphasized, to a second generation, beginning in the late 1970s, influenced by feminist criticism in other disciplines and offering a more complex critique of both art and culture through an investigation of the production and evaluation of art and the role of the artist. In this survey, we propose, first, to outline the history of feminist art and art history, then to discuss the interrelated themes in each, and, finally, in the concluding and pivotal sections (IV and V), to discuss various feminist art-critical and art-historical methodologies.
Keywords: 1900-1999; approches et analyses; art moderne; artistes féministes; arts; corps; cours; critique d'art; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; maternité; patriarcat; premier cycle; périodes historiques; représentation; sexisme; sexualité; systèmes d'oppressions; thématiques

L'avant-garde au feminin: Moscou, Saint-Petersbourg, Paris : 1907-1930 - Marcadé, Jean-Claude; Marcade, Valentine (Artcurial, 1983)
Paris, Artcurial, 1983, broché sous couverture illustrée, 64 pp., (27,5 x 21 cm). Exposition mai-juillet 1983. Importante illustration couleur et noir et blanc (reproductions et photographies). Biographie sommaire autour des artistes :Sonia DELAUNAY, Alexandra EXTER, Marie VASSILIEFF, Marianne WEREFKIN, Natalia GONTCHAROVA, Lioubov POPOVA, Nadiejda OUDALTSOVA, Olga ROZANOVA, Nina KOGAN, Vera PESTEL, Vera ERMOLAIEVA, Xenia ENDER, etc.
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; art moderne; arts; cours; discipline; discours dominant; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; moscou; paris; premier cycle; périodes historiques; russie; régions géographiques; saint-petersbourg; sexisme; systèmes d'oppressions; thématiques

L'autre moitié de l'avant-garde: 1910-1940: femmes peintres et femmes sculpteurs dans les mouvements d'avant-garde historiques - Vergine, Lea (Des Femmes, 1982)
L'autre moitié de l'avant-garde, 1910-1940 est une importante exposition qui s'est tenue à Milan au printemps 1980, puis à Rome, Venise, Amsterdam, Stockholm. D'une rare qualité, elle a remis à jour les démarches et recherches qui, dans la période féconde des années 1930, ont été fondamentales pour l'élaboration d'un langage contemporain. « Préparer ce travail a été, pour moi, une découverte continue : quinze mois passés à chercher dans les caves des musées, à faire ouvrir aux artistes leurs tiroirs. Rares sont les oeuvres que j'ai trouvées accrochées à un mur ! [...] L'exposition évoque les années du Blaue Reiter, du cubisme, du futurisme, du dadaïsme, du Bauhaus. Je voulais voir si les femmes avaient eu ou non, dans ces groupes, la possibilité d'être des forces motrices. Et j'ai découvert, par exemple, que dans l'avant-garde russe, les femmes ont eu un rôle tout à fait décisif...» L.V. Le catalogue rassemble ces monographies, largement illustrées des productions des femmes peintres et sculptrices, et retrace ces mouvements novateurs.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques

The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting--Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz--and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques